2008
DOI: 10.1371/journal.pgen.1000237
|View full text |Cite
|
Sign up to set email alerts
|

Numt-Mediated Double-Strand Break Repair Mitigates Deletions during Primate Genome Evolution

Abstract: Non-homologous end joining (NHEJ) is the major mechanism of double-strand break repair (DSBR) in mammalian cells. NHEJ has traditionally been inferred from experimental systems involving induced double strand breaks (DSBs). Whether or not the spectrum of repair events observed in experimental NHEJ reflects the repair of natural breaks by NHEJ during chromosomal evolution is an unresolved issue. In primate phylogeny, nuclear DNA sequences of mitochondrial origin, numts, are inserted into naturally occurring chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 79 publications
4
123
2
Order By: Relevance
“…During religation, exogenous DNA may be captured in the chromosome, leading to insertion of DNA into the genome. In eukaryotes, DNA inserted into the genome by NHEJ during evolution may include foreign DNA fragments such as mitochondrial DNA, transposable elements, and viral DNA (Moore and Haber 1996;Ricchetti et al 1999;Lin and Waldman 2001a;Lin and Waldman 2001b;Nakai et al 2003;Hazkani-Covo and Covo 2008). The classical eukaryotic NHEJ machinery includes the KU70/80 heterodimer (KU), XRCC4, Ligase IV, and DNA-PKcs proteins (Bassing and Alt 2004;Lieber et al 2004).…”
Section: Recent Lgt Between Distantly Related Speciesmentioning
confidence: 99%
“…During religation, exogenous DNA may be captured in the chromosome, leading to insertion of DNA into the genome. In eukaryotes, DNA inserted into the genome by NHEJ during evolution may include foreign DNA fragments such as mitochondrial DNA, transposable elements, and viral DNA (Moore and Haber 1996;Ricchetti et al 1999;Lin and Waldman 2001a;Lin and Waldman 2001b;Nakai et al 2003;Hazkani-Covo and Covo 2008). The classical eukaryotic NHEJ machinery includes the KU70/80 heterodimer (KU), XRCC4, Ligase IV, and DNA-PKcs proteins (Bassing and Alt 2004;Lieber et al 2004).…”
Section: Recent Lgt Between Distantly Related Speciesmentioning
confidence: 99%
“…It was suggested that the insertion mechanism involves double-strand break repair via NHEJ (Hazkani-Covo and Covo, 2008). The availability of whole-genome sequences of more species has enabled a more detailed study of genomic structure of NUPTs and NUMTs.…”
Section: Introductionmentioning
confidence: 99%
“…No mutation, no evolution, regardless of population size. Gene transfers from endosymbiotic organelles to their host are a mechanism of mutation that is both specific to symbiogenesis and specific to the eukaryotic lineage (124,125,126). Eukaryotes are genetic chimaeras, with more bacterial genes than archaeal genes (127,128,129,130), and gene transfers from mitochondria and chloroplasts continue to permeate eukaryotic chromosomes via known mechanisms -non homologous end joining (126) -that can be observed in the laboratory (131).…”
Section: Gene Transfers From Organellesmentioning
confidence: 99%
“…Gene transfers from the mitochondrial symbiont to host chromosomes were important at eukaryote origin (41). Given what we have learned about the abundance of plastid and mitochondrial DNA in eukaryotic genome sequences (124,125,126,132,133), that set of propositions would seem far less controversial than it did 20 years ago, one would think.…”
Section: Gene Transfers From Organellesmentioning
confidence: 99%
See 1 more Smart Citation